A Polysaccharide From Eupolyphaga sinensis Walker With Anti-HBV Activities In Vitro and In Vivo - Zhang, Xue; Su, Huiling; Yu, Haifei; Ding, Jialu; Deng, Wanyu; Qin, Bo; Zhou, Changlin; Dou, Jie; Guo, Min (Frontiers in Pharmacology, 2022)
Hepatitis B virus (HBV) infection remains a major global threat to human health worldwide. Recently, the antiviral properties and low toxicity of traditional Chinese medicine have been concerned. In our previous study, Eupolyphaga sinensis Walker polysaccharide (ESPS) has been isolated and characterized. While its antiviral effect on HBV remained unclear. The anti-HBV activity of ESPS and its regulatory pathway were investigated on HepG2.2.15 cells and HBV transgenic mice. The data obtained from in vitro studies showed that ESPS significantly inhibited the production of HBsAg, HBeAg and HBV DNA in the supernatants of HepG2.2.15 cells in a dose-dependent manner, HBV RNA and core protein expression were decreased by ESPS, either. In vivo studies further revealed that ESPS (20 and 40 mg/kg. 2 d) significantly reduced the levels HBsAg, HBeAg and HBV DNA in the serum, as well as HBV DNA and HBV RNA in the liver of HBV transgenic mice. In addition, ESPS activated the toll like receptor 4 (TLR4) pathway, then elevated levels of IFN-β，TNF-α and IL-6 in the serum were observed, indicating that the anti-HBV effect of ESPS was achieved by potentiating innate immunity function. In conclusion, our study shows that ESPS is a potential anti-HBV ingredient, which is of great value in the development of new anti-HBV drugs.